A multi-network comparative analysis of whole-transcriptome and translatome reveals the effect of high-fat diet on APP/PS1 mice and the intervention with Chinese medicine - Wenya Gao; Junyi Zhou; Xinru Gu; Yanyan Zhou; Linna Wang; Nan Si; Xiaorui Fan; Baolin Bian; Hongjie Wang; Haiyu Zhao (Frontiers in Nutrition, 2022)
Different studies on the effects of high-fat diet (HFD) on Alzheimer’s disease (AD) pathology have reported conflicting findings. Our previous studies showed HFD could moderate neuroinflammation and had no significant effect on amyloid-β levels or contextual memory on AD mice. To gain more insights into the involvement of HFD, we performed the whole-transcriptome sequencing and ribosome footprints profiling. Combined with competitive endogenous RNA analysis, the transcriptional regulation mechanism of HFD on AD mice was systematically revealed from RNA level. Mmu-miR-450b-3p and mmu-miR-6540-3p might be involved in regulating the expression of Th and Ddc expression. MiR-551b-5p regulated the expression of a variety of genes including Slc18a2 and Igfbp3. The upregulation of Pcsk9 expression in HFD intervention on AD mice might be closely related to the increase of cholesterol in brain tissues, while Huanglian Jiedu Decoction significantly downregulated the expression of Pcsk9. Our data showed the close connection between the alterations of transcriptome and translatome under the effect of HFD, which emphasized the roles of translational and transcriptional regulation were relatively independent. The profiled molecular responses in current study might be valuable resources for advanced understanding of the mechanisms underlying the effect of HFD on AD.